Design of a dual-band rectifier for wireless power transmission - Defu Wang; Renato Negra (2013 IEEE Wireless Power Transfer (WPT), 2013)
This paper presents a dual-band rectifying circuit for wireless power transmission working at 2.45 GHz and 5.8 GHz. A modified dual-band matching network is adopted to realize the highly efficient dual-band rectifier. Source-pull simulations are performed, to determine the proper impedances at the two different frequencies. The proposed dual-band rectifier has been implemented and the measurements show good agreement with simulation. With a dual-band input matching network, the measurement results for an input power level of 10 mW show peak RF-to-DC efficiencies of 66.8 % and 51.5 % at 2.45 GHz and 5.8 GHz respectively.